Comparison of the nutritional and phytochemical composition and antioxidant activities of Aralia elata (Miq.) Seem fruits in Northeast China - Yaqin Tian (Elsevier, 2021)
Aralia elata (Miq.) Seem is a wild medicinal and culinary plant. The newly grown shoots are edible, and the stem and root bark are traditional materials used for medicinal extraction. However, few studies have examined the quality and biological activity of the fruit. In this study, we compared the nutritional and phytochemical composition and antioxidant activity of A. elata fruit (AF) picked from five regions (Harbin, Benxi, Raohe, Jiaohe, and Mudanjiang) in Northeast China. AF picked from Harbin had the highest saponin, anthocyanin, and flavonoid contents. UHPLC-MS/MS analyses showed that araloside A was one of the main saponin monomers in AF. The highest arloside A concentration was detected in fruits picked from Harbin and the lowest concentration was detected in fruits picked from Benxi. The relative reactive oxygen species production in cells after pretreatment with AFs from Harbin (50 μg/mL) was 0.78 ± 0.01, second only to those from Raohe. AFs (50 μg/mL) from Harbin had the highest catalase activity (43.61 ± 0.44 U/mg protein), followed by that of the AF collected from Jiaohe, Benxi, Mudanjiang and Raohe. The malondialdehyde levels of the AFs (50 μg/mL) obtained from Benxi, Raohe, Jiaohe, and Mudanjiang were significantly higher than those of the AF obtained from Harbin (2.67 ± 0.15 nmol/mg protein). Compared with AFs from Benxi, Raohe, Jiaohe, and Mudanjiang, the strongest H2O2 scavenging ability (144.95 ± 2.89 mmol TE/100 g dm) was observed for AF from Harbin. The ferric reducing antioxidant power of AFs ranged from 7.70 to 4.52 mmol TE/100 g dm in the order of Harbin > Mudanjiang > Raohe > Jiaohe > Benxi. The results provided support for the selection of the best quality AF and the expanded cultivation of A. elata.